Settlement of dumping cases within the framework of the World Trade Organization - Abbassi, Siham; Salim, Hamidani; Mouna, Meguellati (The International tax journal, 2025)
The World Trade Organization is an international trade organization that regulates all areas of global trade, including the settlement of trade disputes arising between its members. Among these disputes is anti-dumping disputes, which are among the most prominent trade disputes arising between members. These disputes involve the dumping of a particular commodity in a member's market at a price lower than its cost or less than its value. In this area, the WTO specializes in resolving anti-dumping disputes by following a set of special procedures that are appropriate to the nature of this type of dispute when it comes to international competition with developing countries, given the specific nature of these countries' trade markets.